Constraints Faced by the Mango Growers on Adoption of Recommended Plant Protection Measures - Thakur, Sayali; Shirke, V. S. (Indian Journal of Extension Education, 2015)
The study revealed that lack of technical and scientific guidance regarding plant protection measures, lack of knowledge  regarding quantity and concentrations of chemicals to be used and lack of knowledge regarding identification of pests,  their nature of damage, diseases and their symptoms, unavailability of required insecticides and fungicides at village  level, high cost of plant protection chemicals and equipments, unavailability of plant protection equipments on hire basis,  lack of facilities for repairing plant protection equipments at village level, lack of finance and sudden rainfall after  spraying causes washing off plant protection were the major constraints faced by the mango growers.
Keywords: Constraints; mango growers; adoption